Novel and effective secret sharing scheme - Run-hua SHI; Liu-sheng HUANG; Wei YANG; Hong ZHONG (Tongxin xuebao)
A novel secret sharing scheme was proposed.This scheme consisted of two layer protocols:in the first layer,a larger secret was split into t smaller integers (sub-secrets) based on the Stern-Brocot tree; in the lower layer,t sub-secrets obtained from the first layer were regarded as t initial states in one-dimensional cellular automaton model,and then from the t initial states it could dynamic create all participants’ shares according to the simple fixed rule.This scheme could dynamic add new member,adjust the threshold value and renew the secret and the shares.Besides,there were still other advantages that the costs of the computation were very low and the size of the shares was very small.The results of analysis show that it was secure and very efficient.